ANALISIS SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH (PPKAD) KABUPATEN LAHAT - Restu Inayah; Arista Hakiki; Relasari Relasari (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2016)
This research discussed about the analysis of regional management information system (SIMDA) for finance at Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah) (PPKAD) of Lahat Regency. Data Analysis method used in this research was the qualitative descriptive with the system approach a decipherment from an information system, which is accrual based SIMDA for Finance into part of the components (with the purpose) to identify and evaluate problems, chances, ,obstacles, and needs thus recommendation can be suggested.The result of the research showed that there are excellences, limitations, and internal controls on the regional management information system (SIMDA) for finance at Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah (PPKAD) of Lahat Regency.